Experimental Investigation to Find the Strength of Ballast - Bagas Aryaseta; Fithri Estikhamah (Advance Sustainable Science, Engineering and Technology (ASSET), 2022)
Although ballast is only part of the substructure, it plays an important role in keeping the railway track in position. But less attention has been given to the substructure because the properties of the substructure are more varies and difficult to define than those of the superstructure. Research about ballast behaviours still needs to be developed. Objective of this research is to use Los Angeles Abrasion (LAA) and Aggregate Impact Value (AIV) test to analyse the strength of nature rock (NR), slag (S) and their different combination. Four different types of samples have been prepared for testing. LAA and AIVtest has been performed to assess the strength of the ballast. Finally, the result shows that the combination of slag and nature rock showed good results, even not really significantly. The result for 25%NR+75%S (LAA test) and 1NR+2S (AIV test) is 7,41% and 6,02%, respectively.